ANALISIS KEBUTUHAN KEBIJAKAN DAN KOMPETENSI GURU PADA PENGGUNAAN SMART TV SEBAGAI MEDIA PENDUKUNG PEMBELAJARAN DI SD INPRES 48 KABUPATEN SORONG - Kukuh Arif Styawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The use of digital technology in learning during the Merdeka Curriculum era increasingly encourages elementary schools to integrate modern devices such as Smart TVs as supporting media. This study aims to analyze the school policy needs and teacher competencies in the use of Smart TVs as a supporting learning medium at SD Inpres 48, Sorong Regency. The research employs a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews with classroom teachers who actively use Smart TVs. The findings reveal that the school has established a basic policy, formalized in an official letter, which covers the designated use of the device, permitted content types, and prohibitions against non-educational use. However, this policy has not yet been supplemented by specific internal standard operating procedures (SOPs) and still relies on regulations from the Central Ministry and the Regional Education Office. Currently, only one Smart TV unit is available, located in classroom V A, with funding sourced from the School Operational Assistance (BOS) budget. Teacher competency in technical aspects is considered adequate, covering device operation, wireless display connectivity, and access to educational digital content. The primary needs identified include the addition of more Smart TV units, the development of internal SOPs, and the implementation of ongoing teacher training programs. This study concludes that the utilization of Smart TVs at SD Inpres 48 needs to be supported by more comprehensive policies and structured competency enhancement programs to optimize the quality of learning.